2017
DOI: 10.1002/nha3.20198
|View full text |Cite
|
Sign up to set email alerts
|

An Examination on the Effect of Prior Knowledge, Personal Goals, and Incentive in an Online Employee Training Program

Abstract: This study explored factors that predicted learners' transformative learning in an online employee training program in a higher education institution in the U.S. A multivariate multiple regression analysis was conducted with a sample of 74 adult learners on their learning of a new learning management system. Four types of participants' behaviors were measured and aligned with 3 phases of transformative learning, namely, number of active visits in Phase 1, alignment of personal goals with actual actions in Phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The three individual influences with contradictory effects were learners’ technological self-efficacy, learners’ expectations, and work-related aspects. Although we found that technologically proficient learners spent more time on the online learning management system than less technologically proficient learners, there was no strong relationship between learners’ technological self-efficacy and their completion of online professional learning courses (Gagnon et al, 2007; LoCasale-Crouch et al, 2016; Maor & Volet, 2007; Zha et al, 2017). As LoCasale-Crouch et al (2016, p. 115) suggested, “Perhaps the minimal amount of discomfort participants reported might have provided enough tension to actively engage with but not interfere with course participation.” For learners who had expectations from online professional learning, Zha et al (2017) found that learners were more likely to use the online learning system, but having expectations also could not explain whether learners completed courses.…”
Section: Resultsmentioning
confidence: 61%
See 4 more Smart Citations
“…The three individual influences with contradictory effects were learners’ technological self-efficacy, learners’ expectations, and work-related aspects. Although we found that technologically proficient learners spent more time on the online learning management system than less technologically proficient learners, there was no strong relationship between learners’ technological self-efficacy and their completion of online professional learning courses (Gagnon et al, 2007; LoCasale-Crouch et al, 2016; Maor & Volet, 2007; Zha et al, 2017). As LoCasale-Crouch et al (2016, p. 115) suggested, “Perhaps the minimal amount of discomfort participants reported might have provided enough tension to actively engage with but not interfere with course participation.” For learners who had expectations from online professional learning, Zha et al (2017) found that learners were more likely to use the online learning system, but having expectations also could not explain whether learners completed courses.…”
Section: Resultsmentioning
confidence: 61%
“…Course structure differed by the target industry. Courses that included reflective or interactive activities through discussion forums were in the educational profession (e.g., Bonafini, 2017; Smith & Sivo, 2012; Zha et al, 2017). Alternatively, courses that included problem-based learning and knowledge tests were in the medical professions (e.g., Conte, 2012; Gagnon et al, 2007; Te Pas et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations